Pengaruh pemberdayaan psikologi sumber daya manusia, profesionalisme, terhadap komitmen karyawan - Malinda Septinawati; Yonathan Pongtuluran; Doddy Adhi Mursandi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
Malinda S. Sumadi, 2016 Effect of Human Resources Empowerment Psychology, Professionalism, Commitment Against Employees at PT. Telekomunikasi Indonesia, Tbk Witel Samarinda under the guidance of Mr. Yonathan Pongtuluran and Mr. Doddy Adhimursandi. This study aims to determine whether the Psychology of Human Resources and Professionalism positive and significant impact on employee commitment. The independent variables in this study is the Psychology of Human Resources and professionalism. The dependent variable is the Employee Commitment. This research was conducted at PT. Telekomunikasi Indonesia, Tbk Witel Samarinda consisting of 52 people. This research is quantitative. The data collection is done by collecting a questionnaire to test the Psychology of Human Resources and professionalism. Data were analyzed by using multiple linear regression. These results indicate that employee commitment is backed by the professionalism of the negative and significant while the Psychology of Human Resources no significant effect on employee commitment.Keywords : Psychology Human Resources, Professionalism, and Commitment Employee.